La teoría de juegos conductual, el dilema del viajero alternativo y la maximización de pagos - Rodrigo Moro; Esteban Freidin; Fernando Tohmé; Marcelo Auday (Estudios de Economía, 2011)
– Within the area of Behavioral game theory, we focus on a specific context, namely, on a game we called the Alternative traveler's dilemma. In this context, we observe that participants tend to choose strictly dominated strategies. In order to explain similar tendencies in other games, researchers in the area have postulated either cognitive biases or motivational factors. We postulate a psychological factor called 'goal accessibility bias' to explain the tendencies at stake. This factor involves both cognitive and motivational aspects. We survey a series of experimental results that favor such an explanation over more frugal alternatives.
Keywords: C7; C91; 330; game theory; experiments; maximization; alternative traveler's dilemma; goals; Spieltheorie; Verhaltensökonomik; Urlaubsverhalten